The role of nursing in entrepreneurship in Brazil (Research, Society and Development, 2022)
The aim of this study was to understand the role of nurses in the area, in addition to what types, fields and/or sectors can be undertaken. This is an integrative review of the literature, with the purpose of analyzing the performance of nurses in entrepreneurship sought through databases: LILACS/BDENF, MEDLINE and SCIELO. The inclusion criteria used were: articles published between 2012-2022, in Portuguese and English, available in full, and according to the guide question. Manuals, books, dissertations, theses, monographs, review articles of any kind, editorials and duplicate articles were excluded. The 10 articles show that there are several niches for business nursing, besides that the motivations were surrounded by financial stability, growth in the market, leadership and independence about welfare. Nursing, although consolidated as a profession, needs to seek new fields of activity, not only associated with traditional health hospitals. The Federal Nursing Council (COFEN) encourages these work alternatives aimed at entrepreneurship in the area.